Determination of Trace Amounts of Palladium in Water Samples by Graphite Furnace Atomic Absorption Spectrometry after Dispersive Liquid-Liquid Microextraction - Mohammad Reza Jamali; Yaghoub Assadi; Reyhaneh Rahnama Kozani (Journal of Chemistry)
A simple, rapid, and powerful microextraction technique was used for determination of palladium (II) ion in water samples using dispersive liquid-liquid microextraction (DLLME) followed by graphite furnace atomic absorption spectrometry (GF AAS). The different variables affecting the complexation and extraction conditions such as extraction and disperser solvent type, extraction time, pH, and concentration of chelating agent were optimized. Under the optimum conditions, the calibration graph was linear in the ranges of 0.05–1 μg L−1 with detection limit of 0.02 μg L−1. The precision (RSD %) for ten replicate determination at 0.2 μg L−1 of palladium was better than 3.5% and the enrichment factor 166.5 was obtained from only 5.0 mL of sample. Under the presence of foreign ions, no significant interference was observed. Finally, accuracy and application of the method were estimated by using test samples of natural waters spiked with different amounts of palladium.